2008
DOI: 10.3748/wjg.14.5730
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hepatic progenitors from human fetal liver during second trimester

Abstract: Our study suggests that these EpCAM +ve cells can be used as hepatic progenitors for cell transplantation with a minimum risk of alloreactivity and these cells may serve as a potential source for enrichment of hepatic progenitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 21 publications
0
25
1
Order By: Relevance
“…It was noteworthy that newborn mLEPCs expressed E-cad, CD49f, and nestin, which have been documented as the specific markers of HPCs in many literatures. CD49f has been detected in fetal as well as adult mouse liver, in states of liver disease, and in liver hepatic stem cells (Suzuki et al 2002;Hoppo et al 2004;Rao et al 2008). Nestin, generally recognized as a specific marker for neuroectodermal progenitors, has been detected in foetal hepatic stem cells (Sun and An 2004;Herrera et al 2006) or in proliferating adult hepatocytes (Koenig et al 2006a).…”
Section: Discussionmentioning
confidence: 96%
“…It was noteworthy that newborn mLEPCs expressed E-cad, CD49f, and nestin, which have been documented as the specific markers of HPCs in many literatures. CD49f has been detected in fetal as well as adult mouse liver, in states of liver disease, and in liver hepatic stem cells (Suzuki et al 2002;Hoppo et al 2004;Rao et al 2008). Nestin, generally recognized as a specific marker for neuroectodermal progenitors, has been detected in foetal hepatic stem cells (Sun and An 2004;Herrera et al 2006) or in proliferating adult hepatocytes (Koenig et al 2006a).…”
Section: Discussionmentioning
confidence: 96%
“…Just in 2007, FLSPCs were isolated by MACS with epithelial cell adhesion molecule (EpCAM), which were also CD133 positive [8]. Later in 2008, EpCAM + FLSPCs were demonstrated positive for several markers associated with hepatic progenitor cells including CD49 [23]. Actually, CD49f has been used as an independent marker to isolate FLSPCs [9,24].…”
Section: Discussionmentioning
confidence: 99%
“…The self-renewal capacity of HSCs was demonstrated by phenotypic stability after expansion for more than 150 population doublings in a serum-free, defined medium and with a doubling time of 36 h (36). Recently, several studies have indicated the ability of rapid proliferation and regeneration of liver cells derived from human fetal liver compared with the adult liver (37)(38)(39)(40). Earlier work has shown that treatment for acute liver failure by human fetal hepatocytes is feasible (41).…”
Section: Discussionmentioning
confidence: 99%